Appropriate growth models to describe early growth of Kejobong goat based on Growth Hormone (GH) gene sequence analysis - S. Sutopo; D. A. Lestari; T. Oikawa; T. Konno; E. Purbowati; A. Setiaji; E. Kurnianto (Journal of the Indonesian Tropical Animal Agriculture, 2021)
The objectives of this study were to reveal appropriate growth models describing early growth of Kejobong goat based on Growth Hormone (GH) gene sequence analysis. A total of 35 DNA samples and 1.960 records of quantitative traits of Kejobong goat were collected. The exon 3 of GH gene was amplified and was sequenced to determine the SNP. Body weight and body measurements of the goats were taken at 0-14 weeks of age. Four non-linear growth models were applied for analysis of growth to compare growth performance of different genotypes by Non-Linear Mixed Model. A non-synonymous mutation (g1170AG) genotyped into GG, AG and AA was significantly associated with growth traits. Animals with heterozygous genotype AG showed higher growth traits than animals with homozygous genotype AA. Nonetheless, animals with homozygous genotype GG had the same growth traits with those animals with heterozygous genotype AG and homozygous genotype AA. The most fitted model for describing body weight was Von Bertalanffy model, while for describing wither height and hip height was Brody model. SNP at exon 3 of the GH gene can be used as genetic marker for improvement of growth traits of Kejobong goats.